Transformations of health factors in students aged 18-24 engaging in unprotected sexual behaviour - Agnieszka Kulik; Natalia Kajka; Monika Dacka (The Francis de Sales Scientific Society (TNFS.PL), 2021)
Among the most important tasks for the upcoming decade, WHO (2020) lists the sexual education of young people. The aim of the current research was to recreate the health functioning of Polish university students and to identify the factors that determine why they engage in risky sexual behaviours. The analyses took into account health locus of control, undertaken health activities and attitude to God. 32 people aged 18 to 23 (M = 20.03; SD = 1.15) who did not limit sexual activity without protection qualified for the analyses.  The respondents completed three research tools:  MHLC (Wallston, Wallston & DeVellis 1978), IHB (Juczyński 2012),  CoP (Bartczuk & Zarzycka 2020) and a health survey. As a result of the conducted analyses, three groups of people were selected, characterised by different approaches to sexual activity. The article will present the results of analyses concerning people who do not limit sexual activity without protection. The respondents who belong to this group are characterised by a tendency to over-idealise themselves and their actions. They engage in risky activities, but avoid involvement in health-promoting activities. The present research provides qualitative analyses that help to better understand what factors may affect it.